Syndromic deafness mutations at Asn 14 differentially alter the open stability of Cx26 hemichannels - Sanchez, Helmuth A. (J Gen Physiol, 2016)
Connexin 26 (Cx26) is a transmembrane protein that forms hexameric hemichannels that can function when unopposed or dock to form intercellular gap junction channels. Aberrantly functioning unopposed hemichannels are a common feature of syndromic deafness associated with mutations in Cx26. In this study, we examine two different mutations at the same position in the N-terminal domain of Cx26, N14K and N14Y, which have been reported to produce different phenotypes in patients. We find that both N14K and N14Y, when expressed alone or together with wild-type (WT) Cx26, result in functional hemichannels with widely disparate functional properties. N14K currents are robust, whereas N14Y currents are small. The two mutants also exhibit opposite shifts in voltage-dependent loop gating, such that activation of N14K and N14Y is shifted in the hyperpolarizing and depolarizing directions, respectively. Deactivation kinetics suggests that N14K stabilizes and N14Y destabilizes the open state. Single N14K hemichannel recordings in low extracellular Ca(2+) show no evidence of stable closing transitions associated with loop gating, and N14K hemichannels are insensitive to pH. Together, these properties cause N14K hemichannels to be particularly refractory to closing. Although we find that the unitary conductance of N14K is indistinguishable from WT Cx26, mutagenesis and substituted cysteine accessibility studies suggest that the N14 residue is exposed to the pore and that the differential properties of N14K and N14Y hemichannels likely result from altered electrostatic interactions between the N terminus and the cytoplasmic extension of TM2 in the adjacent subunit. The combined effects that we observe on loop gating and pH regulation may explain the unusual buccal cutaneous manifestations in patients carrying the N14K mutation. Our work also provides new considerations regarding the underlying molecular mechanism of loop gating, which controls hemichannel opening in the plasma membrane.